Analysis Influence of Information Technology on Financial Transparency BAZNAS in Sharia Maqashid Perspective - Suginam; Ahmad Qorib; Saparuddin Siregar; Surya Darma Nasution (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
This research aims to see whether the influence of technology on financial transparency is an effort to be able to build public trust in financial management in accordance with Sharia organizations or not. To give confidence to the public in financial management, it requires disclosure of information to the public as a disclosure of the performance report of an institution or organization. Transparency is a disclosure in the form of financial performance reports that are presented in an open, detailed, clear, easily accessible manner and can be conveyed periodically. This research was conducted based on literature studies from various sources from previous studies. This research method uses a qualitative descriptive research method that will describe the subject under study. The results of this study can be concluded that information technology on financial transparency is in accordance with Islamic maqasit. Abstrak: Penelitian ini mempunyai tujuan untuk mengetahui apakah pengaruh teknologi informasi terhadap transparansi keuangan sebagai salah satu upaya untuk dapat membangun kepercayaan masyarakat dalam pengelolaan keuangan telah sesuai dengan maqasit Syariah atau tidak. Untuk memberikan kepercayaan terhadap public atas pengelolaan keuangan maka diperlukan keterbukaan informasi kepada public sebagai pengungkapan laporan kinerja suatu Lembaga atau organisasi. Tranparansi merupakan pengungkapan dalam bentuk laporan kinerja keuangan yang disampaikan secara terbuka secara rinci, jelas, dapat mudah untuk di akses dan dapat di sampaikan secara periodic. Penelitian ini di lakukan berdasarkan studi literatur dari berbagai sumber dari penelitian-penelitian sebelumnya. Metode penelitian ini menggunakan metode penelitian deskriptif kualitatif yang akan mendeskripsikan dari subjek yang diteliti. Hasil dalam penelitian ini dapat disimpulkan bahwa teknologi informasi terhadap transparansi keuangan telah sesuai dengan maqasit Syariah.